Mulheres gerenciáveis?: uma análise dos discursos sobre as mulheres na revista Exame - Ana Paula Rodrigues Diniz (2012)
In this research we aimed to comprehend the managerial discourses about women as minorities on work space from the analysis of Exame Magazine texts. In order to do so, we began from a feminist and critical approach, compromised with a reflection about how genders are built and crystallized by cultural and discoursive practices, and how social order is created, and how plurality and diversity are overshadowed. As methodological and analitical resource, we used Critical Discourse Analysis, aiming to apprehend the genres, discourses and styles on the texts collected from the last five years of the magazine. As result, we deprehend two main discourses: the expropriated feminist and the reinforced managerialist. Those discourses have similarities and differences related to ways of representation, genres, styles and intertextuality. The relations between them conducted to a heterogeneous discoursive order, constructed around the conflict between femininehomogeneity and plurality, the possibility and the impossibility of use the feminine characteristics as organizational resource, and the representation of work space as favorable and unfavorable for women. In this paradoxal context, we discussed that the discoursive practices aprehended may be seen as destabilizing and constructing the patriarchal structures, contributing to the desconstruction of patriarchal truths and, at the same time, reinforcing the traditional femininity though with new boundaries. However, those practices may be understood as a tool to reinforce the capitalist structures, since they are related with theutilization of characteristics seen as feminines in organizations, and with the exploration of feminine consumer market. In this context, we emphasized the limits of those discourses about women as minorities in job space, reinforcing that they constitute a fallacious proposal in terms of advances for women, since they negociate advances in return of new imprisonments.